2014
DOI: 10.1186/1471-2261-14-37
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin down-regulates the production of Interleukin-8 by neutrophil leukocytes from dyslipidemic patients

Abstract: BackgroundNeutrophil (PMN) leukocytes participate to the initial phases of atherosclerosis through the release of Interleukin 8 (CxCL8; IL-8) that contribute to amplification of inflammation. Aim of the study is to investigate the production of IL-8 by PMN leukocytes from dyslipidemic patients treated with simvastatin.MethodsIn 15 dyslipidemic subjects with moderately increased cardiovascular risk, assessed by Framingham Risk Score, blood samples were obtain to investigate PMNs IL-8 production [at baseline and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…On the other hand, atorvastatin inhibits neutrophil infiltration in the early phase of the atherosclerotic buildup via nitric oxide, and this appears to be independent of any lowering effects on the cholesterol levels [151]. Recent studies on leukocytes isolated from dyslipidemic patients are showing that simvastatin reduced the proinflammatory chemokine IL-8 [152]. In addition, combinational use of an Angiotensin-II receptor blockers [ARB] (telmisartan) with a statin (rosuvastatin) in patients with carotid atherosclerosis showed a remarkable effect on suppressing a wide range of inflammatory factors including IL-1β/2/6/10/17/23, TNF-α, CRP, and MCP-1 [153].…”
Section: Current Pharmacotherapy Targeting Inflammation Before MImentioning
confidence: 97%
“…On the other hand, atorvastatin inhibits neutrophil infiltration in the early phase of the atherosclerotic buildup via nitric oxide, and this appears to be independent of any lowering effects on the cholesterol levels [151]. Recent studies on leukocytes isolated from dyslipidemic patients are showing that simvastatin reduced the proinflammatory chemokine IL-8 [152]. In addition, combinational use of an Angiotensin-II receptor blockers [ARB] (telmisartan) with a statin (rosuvastatin) in patients with carotid atherosclerosis showed a remarkable effect on suppressing a wide range of inflammatory factors including IL-1β/2/6/10/17/23, TNF-α, CRP, and MCP-1 [153].…”
Section: Current Pharmacotherapy Targeting Inflammation Before MImentioning
confidence: 97%
“…Simvastatin was also reported to suppress lymphocyte activation in patients with hypertriglyceridemia [44] . Marino et al [45] reported that simvastatin could suppress IL-8 production from neutrophils in dyslipidemic patients. Simvastatin was also reported to protect dopaminergic neurons in rats with experimentally induced Parkinsonism via suppression of TNF-α production [46] .…”
Section: Discussionmentioning
confidence: 99%
“…Simvastatin has been shown to affect many adverse functions of neutrophils. In a recent study, it has been shown that simvastatin downregulated secretion of interleukin-8 (IL-8) by neutrophils from the dyslipidemic patients ( 281 ). In addition to targeting specialized cells, some other miscellaneous strategies can also be used for the possible management of soot- and CB-associated toxicity.…”
Section: Possible Therapeutic Interventions To Combat Soot- or Cb-assmentioning
confidence: 99%